ANALISIS KEMAMPUAN SALURAN DRAINASE TERHADAP GENANGAN BANJIR DI JALAN GUNUNG BUNGKUK KOTA BENGKULU DENGAN MENGGUNAKAN APLIKASI EPA SWMM 5.1 - Hendy Apriyanza; Khairul Amri; Gusta Gunawan (Universitas Bengkulu, 2019)
This study aims to determine the flood discharge plan, discharge the existing channel and analyze the condition of the existing channel and look for alternatives to handling flood inundation at the location of flood inundation. Retrieval of data by measuring the existing channel in the flood inundation location. Calculation of peak discharge uses rational methods for various times of plan return. Rainfall calculation results of the plan that meets the requirements are type 1 Gumbel Method. The results of the research and calculations areknown that the amount of existing channel discharge in seven locations of flood inundation ie left and right Mountain Bambat Road is 0.934 m3 / sec and 3.798 m3 / sec. 2,261 m3 / sec, the left and right Gunung Bungkuk Roads are 0.134 m3 / sec and 0.164 m3 / sec while the flood discharge is 1.897 m3 / sec, Gunung Bungkuk 1 Road is 0.30 m3 / sec while the flood discharge is 0.471 m3 / sec, Gunung Bungkuk Road 4 hunchback of 0.190 m3 / sec while the flooddischarge is 1,336 m3 / sec and Gunung Bungkuk Road is 4 0,173 m3 / sec while the flood discharge is 0,864 m3 / sec and for the drainage of Jalan Gunung Bungkuk is not calculated the channel discharge is due to the channel being closed so that the channel dimension not obtained but for the flood discharge of 2.230 m3 / sec and 0.447 m3 / sec. Thus, it shows that the existing discharge channel on the existing Gunung Bungkuk Hump Mountain Road is unable toaccommodate the planned flood discharge. The alternative to flood inundation is by re-planning drainage channels, channel normalization activities, and improving coordination between the government and the community in maintaining drainage channels.